Survival analysis of sow longevity and lifetime reproductive performance – Review - Soltész, Angéla; Baginé Hunyadi, Ágnes; Kusza, Szilvia; Balogh, Péter (Acta Agraria Debreceniensis, 2016)
Sow longevity plays an important role in economically efficient piglet production. Improving sow longevity results increase in the productivity and profitability of a sow herd. Longevity is a complex trait with many factors that can contribute to a sow having a long and productive life. Not only the sow’s genetics, but also nutrition, environment and the management policies are important. In addition, the removal of non-productive sows along with the introduction of replacement gilts is an essential part of maintaining herd productivity at a constantly high level. The objective of this paper was to summarize the current knowledge about the sow longevity and lifetime performance values, as well as, discusses the survival analysis methods for sow longevity traits. This method can estimate the hazard rate indicating proportional risk of sows being culled at any given time, in addition, it is able to investigate the effects of different factors on longevity. Identifying factors that influence the longevity could assist many commercial pig producers in becoming more efficient.